Resilience as a mediator in the relationship between ambidextrous leadership and nurses’ positive attitudes towards artificial intelligence - Heba Emad El-Gazar; Eman Sameh AbdElhay; Islam Sameh Abdelhay; Mohamed Ali Zoromba (BMC Nursing)
Abstract Background Leadership plays a pivotal role in adopting new trends within the nursing domain. Yet, the impact of ambidextrous leadership on nurses’ positive attitudes towards artificial intelligence is not well understood. Furthermore, the underlying mechanism governing this relationship has not been thoroughly explored. Aim This study aimed to assess the mediating role of resilience in the relationship between ambidextrous leadership and nurses’ positive attitudes towards artificial intelligence. Methods A cross-sectional study was conducted among 208 nurses from a university hospital in Egypt. The Ambidextrous Leadership Scale, the Connor Davidson Resilience Scale, and the Positive Attitudes Towards Artificial Intelligence Scale were used for data collection. Structural equation modeling was applied for data analysis. Results Resilience partially mediated the relationship between ambidextrous leadership and nurses’ positive attitudes towards artificial intelligence. Conclusion Fostering ambidexterity in nurse leaders enhances the resilience of nurses, which in turn, contributes to nurses’ positive attitudes towards artificial intelligence. Clinical trial number Not applicable.